Psychosocial factors of different health behaviour patterns in adolescents: association with overweight and weight control behaviours. - Matos, Margarida Gaspar de (2021)
Physical activity, nutrition, and sedentary behaviour combine to influence the risk of overweight among adolescents. This paper aims to identify psychosocial factors of different health behaviour patterns in adolescents and its association with overweight and weight control behaviours. The 3069 adolescents of both genders (average of 14.8 years old) from the 2010 Portuguese survey of Health Behaviour School-Aged Children (HBSC) answered the 2010 HBSC self-reported questionnaire. It used the cluster k-means (nonhierarchy method), qui-square, one-way ANOVA, and logistic regression. Three clusters with different behavioural patterns (physical activity, sedentary, and eating) composed the results obtained. The sedentary group (34%) had lower self-regulation, body satisfaction, health and wellness, family and classmates relationships, communication with the father than the other two groups. The active gamers (25%) had a smaller BMI but used more unhealthy weight control strategies than the other two groups. The healthy group (41%) was more motivated and more satisfied with school but was not different than the active gamers in most psychosocial variables. Differences were found between clusters for weight control behaviours and psychosocial variables. Different strategies for different patterns were necessary in order to promote obesity prevention and, simultaneously, target healthy lifestyle and wellbeing in adolescents.